Vitamin D supplementation in critically ill patients: pros and cons - Abdolreza Norouzy; M Arabi (World Nutrition Journal, 2023)
Traumatic Brain Injury (TBI) is a leading cause of death in patients admitted to the intensive care unit. Vitamin D or calciferol is a steroidal compound made of cholesterol with healing properties due to its specific receptors (vitamin D receptors) in the nucleus of brain cells and its protective properties against nervous tissue in addition to its anti-inflammatory effects. This study is a double-blind randomized clinical trial that was performed on 72 patients with severe brain injury with a mean age of 34-50 years. They were randomly assigned to the study, thus intervention and control groups received vitamin D with a dose of 100,000 units and a dose of 1000 units for 5 days, respectively.